Strengthening Digital Competence, Business Sustainability, and Organizational Competitiveness in the AI Era: An Interdisciplinary Perspective - Muhamad Akbar (Yayasan Daarul Huda Kruengmane, 2026)
This activity aims to comprehensively examine the relationship between digital competence, business sustainability, and organizational competitiveness through an interdisciplinary approach that integrates perspectives from management, information systems, human resources, and technological innovation. The method used in this activity involves presentations by speakers on current insights and concepts relevant to digital transformation, organizational capabilities, and the utilization of AI in both business and public sector contexts. The results of the discussion indicate that digital competence not only includes technical skills in using technology but also encompasses analytical, adaptive, and strategic abilities in data-driven decision-making. This seminar is expected to contribute conceptually to the development of interdisciplinary studies and serve as a reference for practitioners and policymakers in formulating strategies to strengthen digital competencies in the AI era. Recognizing the importance of this issue, a community service seminar titled “Strengthening Digital Competence, Business Sustainability, and Organizational Competitiveness in the AI Era: An Interdisciplinary Perspective” was held on December 13, 2025. The seminar thoroughly discussed strategies, analyses, and research findings presented by academic speakers in the fields of digital competence and business sustainability. It also highlighted how organizations that enhance their digital capacity and competencies are better prepared to face the challenges of digitalization.